The high-frequency limit of usable response spectral ordinates from filtered analogue and digital strong-motion accelograms. - Akkar, Sinan (Earthquake engineering & structural dynamics.)
The range of response frequencies for which spectral ordinates obtained from accelerograms may be considered reliable is limited by several factors, primary among them being the effects of filters that are routinely applied to remove noise from the records. Considerable attention has been focused on the low-frequency limit of the usable spectral ordinates because of various engineering applications requiring long period spectral accelerations or displacements but only recently have rational approaches to selecting the high frequency limit been proposed. Since there are applications for which the high frequency spectral ordinates are important, the approaches to this issue presented in the recent studies are reviewed and their application to the ground motion database from Europe and the Middle East is explored. On the basis of the results of these analyses, it is concluded that a large proportion of this dataset can be used to provide reliable estimates of response spectral ordinates at much shorter periods than may have previously been considered feasible.